2021
DOI: 10.1101/2021.06.25.450001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated Action of Multiple Transporters in the Acquisition of Essential Cationic Amino Acids by the Intracellular Parasite Toxoplasma gondii

Abstract: Intracellular parasites of the phylum Apicomplexa are dependent on the scavenging of essential amino acids from their hosts. We previously identified a large family of apicomplexan-specific plasma membrane-localized amino acid transporters, the ApiATs, and showed that the Toxoplasma gondii transporter TgApiAT1 functions in the selective uptake of arginine. TgApiAT1 is essential for parasite virulence, but dispensable for parasite growth in medium containing high concentrations of arginine, indicating the prese… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…In contrast to NPT1, a lack of AT6-1 could not be rescued by providing high levels of exogenous lysine, indicating that AT6-1 is the sole lysine transporter of T. gondii. We further observed a modest but significant decrease in arginine uptake upon the down-regulation of AT6-1, consistent with its role as a low affinity arginine transporter [26,27]. To the best of our knowledge, this is the first study employing untargeted metabolomics to characterize an apicomplexan solute carrier.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In contrast to NPT1, a lack of AT6-1 could not be rescued by providing high levels of exogenous lysine, indicating that AT6-1 is the sole lysine transporter of T. gondii. We further observed a modest but significant decrease in arginine uptake upon the down-regulation of AT6-1, consistent with its role as a low affinity arginine transporter [26,27]. To the best of our knowledge, this is the first study employing untargeted metabolomics to characterize an apicomplexan solute carrier.…”
Section: Discussionsupporting
confidence: 77%
“…TgApiAT1 and TgApiAT5-3 were identified as arginine and tyrosine transporters, respectively [11,12]. TgApiAT6-1 was recently putatively characterized as a lysine transporter [26,27]. (b) Cartoon scheme of AT6-1 locus modification by in-Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. falciparum possesses five of the eleven ApiAT subfamilies: Pf ApiAT2 ( Pf ApiAT2/MFR4: PF3D7_0914700), Pf ApiAT4 (MFR5: PF3D7_1129900), Pf ApiAT8 (NPT1: PF3D7_0104800), Pf ApiAT9 (MFR2: PF3D7_0104700) and Pf ApiAT10 (MFR3: PF3D7_0312500). Previous work in the rodent malaria species Plasmodium berghei ( Pb ) and the related Apicomplexan parasite Toxoplasma gondii ( Tg ) showed that Pb ApiAT8 (or Pb NPT1) and several other Tg ApiATs are localized at the PPM 29–32 and possess amino acid transport activity 25,26,2934 . To date, only Pb ApiAT4 has been shown to play an important role in parasite proliferation within erythrocytes 35 .…”
Section: Introductionmentioning
confidence: 99%